In vitro Investigation of Resin Tag Lengths of Three Commercially Available Pit and Fissure Sealants - Nayan J. Sahu; Pratyaksha S. Panwar; Nupur R. Dhanak; P V Samir; Ajmal Najeeb; Deepa Rayast (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of this in vitro study was to perform a comparative evaluation of the length of resin tags produced by three different types of pit and fissure sealants (Embrace WetBond, Helioseal Clear, and Fuji VII) using scanning electron microscopy. Materials and Methods: Thirty extracted mandibular premolars were randomly divided into three groups of ten. Each group was treated with one of the sealants - Embrace WetBond, Helioseal Clear, or Fuji VII. Following cleaning and preparation, the sealants were applied according to the manufacturer's instructions. Teeth were then sectioned and prepared for SEM investigation, and the length of resin tags was measured. Results: Scanning electron microscopy revealed Embrace WetBond produced significantly longer resin tags than Helioseal Clear and Fuji VII. Conclusion: The study concludes that Embrace WetBond sealant exhibited the longest resin tags, which may suggest a stronger mechanical bond to enamel.